Individual minds create universal patterns exploring word order universals using an artificial language learning experiment - Spätgens, Tessa (The University of Edinburgh, 2011)
In recent years, the interest of language universals for researchers of language evolution has been pointed out in various publications. Word order universals are particularly robust examples, and the present dissertation focuses on the relation between the order of the verb and the object and the adposition and the noun. In the languages of the world, there is a preference for consistent ordering of the heads in these constituents. An artificial language learning experiment was conducted, in which participants learned one of four different miniature languages, which represented each of the possible order combinations. The results showed a combined influence of an ordering bias and the native language, showing that the head-order bias involved is strong enough to overcome native language influence. Additional interesting findings on the driving force of the verb phrase order towards other word orders are also discussed. The present study lends support to the hypothesis that language universals are the manifestation of biases on the individual level.
Keywords: universal patterns; artificial language learning